An integrative taxonomic approach to infer the systematic position of Chalepotaxis Ancey, 1887 (Gastropoda: Stylommatophora: Helicarionidae). (3rd April 2017) - Páll-Gergely, Barna; Fehér, Zoltán; Otani, Jamen Uiriamu; Asami, Takahiro
ABSTRACT: In the absence of knowledge about its anatomy, the systematic position of the genus Chalepotaxis, which inhabits a large part of South East Asia, has been historically dubious. The genitalia, sole of the foot and the caudal region of the type species, Chalepotaxis infantilis (Gredler, V. 1881. Zur Conchylien-Fauna von China. III. Stück. Jahrbücher der Deutschen Malakozoologischen Gesellschaft 8, 110–128), are described, which place this genus into the Helicarionidae family. DNA markers (cytochrome oxidase subunit I [COI] and 28S rRNA genes) corroborate this assignment and unequivocally remove the species from the Camaenidae (=Bradybaenidae) and Ariophantidae, where it had previously been placed. Radular morphology of the type species is also re-described and illustrated.